Organizational Satisfaction And Participation: Findings from a Study Of ACE Members - Clifford W. Scherer; Napoleon K. Juanillo Jr. (Journal of Applied Communications, 1989)
Organizations which serve information professionals, such as Agricultural Communicators in Education, must continue to respond to the needs of members through relevant programs and professional opportunities. The study reported here examines satisfaction and participation within the organization. Overall, the study found broad-based member satisfaction. But while there is widespread support, there are segments of the membership which need attention. Findings also identify organizational areas which can be improved, particularly in the conduct of the Critique and Awards Program and in meeting the expectations of members involved in Special Interest Groups (SIG). Specific questions that may have organizational policy implications are raised. The study's finding that member participation positively is related to overall satisfaction with ACE is encouraging. One important goal for ACE, then, would be to encourage increased participation. And, because newer members tend to be the most dissatisfied with ACE, emphasis should be placed on immediately getting them more involved in ACE activities.